Counterfeit, drugs, and human rights: Six parties at an impass? After the extension of the US agenda on North Korea - Hanns Günther Hilpert; Kay Moeller (Stiftung Wissenschaft und Politik (SWP), 2005)
The Bush administration's decision to address Pyongyang's criminal activities and human rights violations could cause a crisis in the Six Party Talks on North Korea's nuclear programme. If the United States does not respond to demands made by both Koreas to discuss these issues bilaterally and separately from the nuclear negotiations, it could be signalling a withering interest in the peaceful agreed denuclearisation of the Kim Chung-il regime. (SWP Comments / SWP)
Keywords: 320